El método Doman en la enseñanza de la lectura en la Educación Básica - Guarnizo Samaniego, Andrea Yolanda (2024)
The Doman Method in the teaching of reading in General Basic Education has been the central focus of the present Curricular Integration Work, carried out in the Educational Unit "José Ángel Palacio" of Loja, during the period 2023-2024. The general objective proposed to determine the influence of the Doman Method in the reading of the students of the Second Grade of General Basic Education, parallel "B". The specific objectives included diagnosing the reading level of second grade, designing a methodological proposal based on the Doman Method and executing said proposal to strengthen the students' reading ability. The research was carried out using a quantitative and qualitative methodology, beginning with a diagnostic evaluation of the students' reading level. Initial results showed that a significant percentage of the students presented reading difficulties. In response, a proposal based on the Doman Method was designed and applied, which was implemented in the grade investigated. The final results showed a remarkable improvement in the students' reading ability, confirming the effectiveness of the Doman Method in this educational context. It is concluded that the Doman Method is an effective tool to improve reading in the children of second grade. In addition, the implementation of this method requires a stimulating and playful environment to maximize its benefits.